STUDENTS’ MEANING-MAKING OF MERDEKA BELAJAR IN ISLAMIC RELIGIOUS EDUCATION WITHIN NAHDLATUL ULAMA–AFFILIATED SCHOOLS - Ridwan; Muh. Azkar; Maimun (El Midad, 2025)
This study aims to examine students’ meaning-making of the Merdeka Belajar (Freedom to Learn) concept in Islamic Religious Education (IRE), particularly within the context of integrating IRE and Aswaja (Ahl al-Sunnah wa al-Jamā‘ah) in educational institutions under the auspices of LP Ma’arif NU, by comparing the experiences of Ahmadiyah minority students and Nahdlatul Ulama–affiliated majority students. Adopting a constructivist paradigm, this research employs a qualitative phenomenological approach. Data were collected through in-depth interviews, observations, and document analysis involving 29 students, teachers, parents, and relevant institutional documents across several schools in Lombok and Madura. Data trustworthiness was ensured through source and methodological triangulation. The findings indicate that students generally perceive IRE–Aswaja learning positively, viewing it as moderate, contextually relevant, and conducive to fostering tolerance and openness of thought. Nevertheless, students’ interpretations of Merdeka Belajar are inherently relative, as they are shaped by the strong socio-ideological construction of Nahdlatul Ulama manifested through the curriculum, school culture, symbolic representations, and familial environments. Consequently, IRE–Aswaja learning functions not only as a means of transmitting religious knowledge but also as a mechanism for shaping students’ religious identity and habitus.